2003
DOI: 10.1080/02652030310001605979
|View full text |Cite
|
Sign up to set email alerts
|

Fate of ochratoxin A in the processing of whole wheat grains during milling and bread production

Abstract: Batches of whole wheat contaminated with ochratoxin A were produced by inoculation with Penicillium verrucosum under controlled conditions in the laboratory. The fate of ochratoxin was followed through initial cleaning, abrasive scouring of the outer grain coat, milling into wholemeal wheat or into 10 milled fractions. Bread was baked from both wholemeal flour and straight-run white flour. Concentrations of ochratoxin A in the cleanings, scourings, and the bran and offal fractions were increased, but reduced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
79
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(88 citation statements)
references
References 8 publications
6
79
1
2
Order By: Relevance
“…Muitos destes alimentos são grãos, como cevada, milho, centeio, trigo e aveia (JORGENSEN; JACOBSEN, 2002), além de estar presente em outros produtos incluindo café, especiarias, nozes, azeitonas, uvas, e figos (BATTILANI et al, 2003;BATISTA et al, 2003;BAYMAN et al, 2002;JORGENSEN, 1998). A ocratoxina sobrevive a processamentos e pode ser encontrada em pães (SCUDAMORE; BANKS; MCDONALD, 2003), café bebida (PITTET, et al, 1996), vinhos (CABAÑES et al, 2002NAICKER, 2002).…”
Section: Introductionunclassified
“…Muitos destes alimentos são grãos, como cevada, milho, centeio, trigo e aveia (JORGENSEN; JACOBSEN, 2002), além de estar presente em outros produtos incluindo café, especiarias, nozes, azeitonas, uvas, e figos (BATTILANI et al, 2003;BATISTA et al, 2003;BAYMAN et al, 2002;JORGENSEN, 1998). A ocratoxina sobrevive a processamentos e pode ser encontrada em pães (SCUDAMORE; BANKS; MCDONALD, 2003), café bebida (PITTET, et al, 1996), vinhos (CABAÑES et al, 2002NAICKER, 2002).…”
Section: Introductionunclassified
“…The extrusion processing, largely used in breakfast cereal production, can also reduce the levels of OTA. Scudamore et al studied the stability of OTA during extrusion of contaminated whole meal wheat flour, observing that a higher temperature, a long contact time and high moisture content were related to a bigger OTA reduction with a maximum loss observed no greater than 40% of the initial amount [46,49]. In the case of rice, it has been observed that OTA contamination level, similarly to the AFs, can be reduced up to 86% if the rice is cooked using a large amount of water [28].…”
Section: Ochratoxin Amentioning
confidence: 99%
“…Bullerman et al studied the degradation of FB1 during the extrusion treatment: an uncontaminated corn grits, grits spiked with 30 μg/g FB1, and grits fermented with Fusarium verticillioides (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) μg/g FB1) were extruded in presence and in absence of glucose (10%, w/w) using a single-screw extruder [101]. The extrusion grits cooking caused significant reduction of FB1 in all treatments if compared with the not extruded used as control.…”
Section: Fumonisinsmentioning
confidence: 99%
See 1 more Smart Citation
“…All those procedures require a suitable sample extraction step using chloroform mixed with orthophosphoric acid 15 , or methanol 16 . For other foods, such as cereals, acetonitrile-water was tried for barley 17 , for various cereals 18,19 , or for wheat grains 20 , at different proportions.…”
Section: Introductionmentioning
confidence: 99%